(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Background: T.B is very important clinical state which can involve any organ of the body. Term EPTB is used to describe the T.B of other organs rather than lungs. Objective: The objective of this study is to see the frequency of EPTB in different organs of the body with relation to family and past history and ratio of EPTB and PTB. Methods: We performed observational study in 167 patients presented with EPTB in outdoor department of Gulab Devi Hospital Lahore. Diagnosis were made by different investigations, then we compared the frequency of EPTB in various organs of the body in relationship with sex and contact and past history. Results: Total patients are 167 out of which 75(44.9%) are females and 92(55.1%) are males. Mean age of all patients is 32.28 years. Most common clinical presentation of extra pulmonary T.B was Pleura effusion74(44.3%), patients presented with T.B of the joints were 39(23.4%).Other organs involved were abdomen, lymph nodes, brain and pericardium. Patients who were reported with abscess and disseminated T.B accounts only for 1.8% of all reported cases. Patients presented with T.B of eye were only 0.6% of all patients.22 (13.17%) patients have positive contact history and 13(7.78%) patients were presentation with previous history of T.B. Conclusion: Most common clinical presentation of EPTB is pleural effusion in age group of 20-40 years in both sex.